The importance of abilities in inclusive experiences from the perspective of people with visual impairments: the example of alpine skiing - Oldörp, Felix; Schaller, Theresa; Grenier, Michelle; Giese, Martin (Frontiers in Sports and Active Living, 2025)
BackgroundAlpine skiing offers both opportunities and challenges for individuals with visual impairments. Despite its potential for inclusion, barriers persist that limit participation. Using an ableism-critical and interpretivist perspective, this study explores inclusion as a subjective experience from the perspective of alpine skiers with visual impairments, focusing on how sport-related abilities influence inclusive processes. The aim is to derive implications for the development of more inclusive sports practices.MethodsA qualitative approach was used, drawing on episodic interviews with six adult skiers (five women, one man) with visual impairment from Germany, including both recreational to competitive athletes. A qualitative content analysis identified key themes related to skiing, abilities, and inclusion.ResultsA synthesis of the interview results revealed four key themes: (1) skiing as a booster for self-confidence, (2) skiing as proof of expertise and competence, (3) skiing under the radar, (4) skiing as a pathway to accessibility and inclusion. Participants reported increased self-confidence, improved motor and social skills, and enhanced advocacy for accessibility. While skiing itself was seen as inclusive, structural barriers including a lack of guides, a limited awareness of para-skiing, and segregated competitions restricted full participation. Conversations with sighted individuals revealed admiration for skiers’ abilities while but also exposed gaps in their understanding of adaptive skiing.ConclusionsSkiing fosters independence, competence, and inclusion for individuals with visual impairment by enhancing skills and challenging ableist perceptions. However, systemic barriers, limited coverage and separate competitive structures, hinder full inclusion—as defined by the United Nations Convention on the Rights of Persons with Disabilities (UN CRPD)—and influence the subjective feeling of inclusion. Addressing these challenges requires greater awareness, improved access to guiding and policy changes to ensure equal participation. This study contributes to the discussion on ability, ableism, and the role of sports in inclusive practices.